1978
DOI: 10.1159/000465242
|View full text |Cite
|
Sign up to set email alerts
|

Serological, Immunochemical and Immuoncytological Properties of Granulocyte Antibodies

Abstract: The immunochemical characteristics of granulocyte alio- and autoantibodies can easily be studied with indirect immunofluorescence techniques. The correlation of these properties with the serological behavior of the antibodies and the clinical condition in which they were found was studied. The investigations included the determination of immunoglobulin class, subclass, light-chain composition, as well as optimal temperature of activity. Complement fixation in vitro was also investigated. Striking differences w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 10 publications
0
27
1
Order By: Relevance
“…15 Therefore, the combination of semiquantified GIIFT and agglutination test for detecting antineutrophil antibodies provide information for predicting the clinical course of children with chronic neutropenia. Further, a large prospective study is necessary to demonstrate that measurement of autoantibodies at the time of diagnosis will aid in observations of the natural history of this disorder.…”
Section: Chronic Neutropenia In Childhood 3469mentioning
confidence: 99%
See 1 more Smart Citation
“…15 Therefore, the combination of semiquantified GIIFT and agglutination test for detecting antineutrophil antibodies provide information for predicting the clinical course of children with chronic neutropenia. Further, a large prospective study is necessary to demonstrate that measurement of autoantibodies at the time of diagnosis will aid in observations of the natural history of this disorder.…”
Section: Chronic Neutropenia In Childhood 3469mentioning
confidence: 99%
“…3,4,7 Several methods are used in the detection of serum antineutrophil antibodies. [5][6][7][8][12][13][14][15][16][17] However, the specificity and sensitivity of these methods have not been well established. In this study, we have developed a method to semiquantify the strength of antineutrophil antibodies by flow cytometric analysis of the granulocyte indirect immunofluorescence test (GIIFT) by using same donor neutrophils.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] It shows the unique feature of being expressed on a neutrophil subpopulation ranging from 0% to 100%. 5 After identification of NB1 GP deficiency as the result of a splicing defect resulting in mRNA strands containing intron sequences with stop codons, we searched for the reason for its heterogeneous expression. 6 For this, we separated the 2 subpopulations by 2 different methods (laser-assisted microdissection and fluorescence-activated cell sorter), followed by qualitative and quantitative measurements of the mRNA content.…”
Section: Introductionmentioning
confidence: 99%
“…Verheugt et al (4) suggested that strongly positive reactions in immunofluorescence were obtained not only with antisera containing agglutinins or granulocytotoxins, but also with some sera that did not react in either the agglutination or cytotoxicity test. In addition, immunofluorescence test appears to be a simple and sensitive method that allows us to study immunochemical characteristics of antibodies (19). In this study, antibodies detected with the agglutination test clearly discriminated between NAl + and NAl-neutrophils.…”
Section: Discussionmentioning
confidence: 53%